Pemanfaatan Digital Marketing Bagi Usaha Mikro, Kecil, Dan Menengah (UMKM) Di Kelurahan Malaka Sari, Duren Sawit - Purwana, Dedi; Rahmi, R; Aditya, Shandy (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2017)
The aim of this study is to improve knowledge and skill about digital marketing, especially social media, for Small and Medium-sized Enterprises (SMEs) business maker to enhance their sales and profit. Attended by 13 women SMEs participants, the method used in this activity is; first, explanation using power point slides and LCD projector; second, experience sharing and discussion; and last, direct practice of creating social media (Facebook and Instagram) account and how to make it attractive for buyers (the pictures, the wording, the story, etc). Held on May 7, 2017, the community service is funded by DIPA BLU Faculty of Economics, Universitas Negeri Jakarta. The result shows that only few who actively use social media as their promotion tools and they have not separated their online shop account with their personal account, several others use it occasionally, and the rest participants have never used social media marketing for being lack of technological skill. All participants show great interest to use social media marketing continuously. KATA KUNCI: digital marketing, UMKM, social media